OPTIMASI VALUASI EKONOMI ENDAPAN NIKEL LATERIT MEMPERHITUNGKAN BIAYA LINGKUNGAN: OPTIMIZATION OF THE ECONOMIC VALUATION OF LATERITIC NICKEL DEPOSITS CONSIDERING ENVIRONMENTAL COSTS - Wahyu Sasongko; Rheva Dwiky Adhitya (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2022)
Optimization of mineral economic valuation aims to determine the maximum net present value of a project over the life of mine. The economic valuation optimization model in this study is the development of the Lane (1988) and Sasongko (2013) model by considering environmental costs and referring to the cash flow framework. The research methods are include the following: (1) resource modeling and estimation, (2) mineral economic valuation modeling, (3) solution model determination, and (4) mineral economic valuation. Resource modeling in the block model with a size of 25 m x 25 m x 1 m. The block content estimation uses the inverse distance weighting (IDW) interpolation method. Economic valuation optimization modeling in this research is modeling in terms of cash flow by considering environmental costs and government policies such as taxes, royalties, and depreciation. Optimizing cut-off grade is an attempt to determine the optimum grade that will produce the maximum profit or net present value (NPV). The solution model in this case includes cut-off grade optimization for profit optimization and NPV optimization. The model solution to determine the optimum cut-off grade depends on constrains of the mining, concentrating and refining. Determination of the cut-off grade optimization model solution using analytical methods. In the case study, the estimated amount is US4,253,566 tons of nickel ore. At a constant mining rate at an optimum level of 0.95%, the mine life is 4.85 years with an NPV of US811,248,447. Optimization of economic valuation with NPV indicator, the life of mine of 4.44 years and maximum NPV of US841,596,460. The cut-off grade value varies in each mining year: the 1st year with a grade of 0.99%; 2nd year level 0.99; 3rd year level 0.98%; 4th year level 0.97%; 5th year the rate is 0.95%. NPV economic valuation optimization has a greater value and shorter time, compared to profit optimization (profit).